2005
DOI: 10.1890/04-0902
|View full text |Cite
|
Sign up to set email alerts
|

Historical Range of Variability in Landscape Structure: A Simulation Study in Oregon, Usa

Abstract: We estimated the historical range of variability (HRV) of forest landscape structure under natural disturbance regimes at the scale of a physiographic province (Oregon Coast Range, 2 million ha) and evaluated the similarity to HRV of current and future landscapes under alternative management scenarios. We used a stochastic fire simulation model to simulate presettlement landscapes and quantified the HRV of landscape structure using multivariate analysis of landscape metrics. We examined two alternative policy … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
68
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 76 publications
(68 citation statements)
references
References 88 publications
0
68
0
Order By: Relevance
“…Multiple studies have identified and used HRV in forest structures and processes to help guide management and conservation of biodiversity. These studies have been done for many regions of the western United States, including the southwest (Moore et al 1999, Swetnam et al 1999, the Oregon Cascades (Cissel et al 1999), the Sierra Nevada (Millar and Woolfenden 1999), the sequoia forest area of California (Stephenson 1999), and the Oregon Coast Range (Wimberly et al 2000, Nonaka andSpies 2005). Landres et al (1999) provide an overview of the natural variability concepts underlying biodiversity management.…”
Section: Background: Historical Range Of Variabilitymentioning
confidence: 99%
“…Multiple studies have identified and used HRV in forest structures and processes to help guide management and conservation of biodiversity. These studies have been done for many regions of the western United States, including the southwest (Moore et al 1999, Swetnam et al 1999, the Oregon Cascades (Cissel et al 1999), the Sierra Nevada (Millar and Woolfenden 1999), the sequoia forest area of California (Stephenson 1999), and the Oregon Coast Range (Wimberly et al 2000, Nonaka andSpies 2005). Landres et al (1999) provide an overview of the natural variability concepts underlying biodiversity management.…”
Section: Background: Historical Range Of Variabilitymentioning
confidence: 99%
“…Wallin and others (1994) demonstrated that shifts from a dispersed to an aggregated harvest pattern did not immediately result in a change in forest attributes such as patch size and edge density. Similarly, Nonaka and Spies (2005) found that more than 100 years was required for the system to regain its historical condition in the absence of human management. Ecologically, the interactions between spatial legacies and new management practices can push forest landscape patterns out of their historical range of variability (Paine and others 1998;Schrö der and others 2005), alter successional pathways, and change regional patterns of forest composition (Hessburg and others 1999;Friedman and Reich 2005).…”
Section: Legacy Durationmentioning
confidence: 99%
“…Instead, it appears that reducing historical time series could be a viable option for land managers who cannot store or manage large historical data sets. This is especially important as more land managers obtain their HRV time series from simulation modeling (Keane and others 2002;Nonaka and Spies 2005;Wimberly and others 2000) because models can produce extensive outputs of simulated historical conditions. However, these synthesis options could result in less variability in the historical record that may make it difficult to detect subtle changes in the reference landscape.…”
Section: Discussionmentioning
confidence: 99%